The Influence “Speak English Today” Channel Podcast on Student Speaking Skill at Mts At-Taqwa 17 Bekasi - Junita, Rahmawati; Hidayati, Dini; Chairiyani, Ika (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to determine the effect of using the “Speak English Today” podcast on the speaking skills of eighth-grade students at MTs At-Taqwa 17 Bekasi. This study uses a quantitative method with a quasi-experimental design. Two classes were selected using purposive sampling: one experimental class taught using the Speak English Today podcast and one control class taught conventionally. Data were collected through pretest and posttest assessments. The posttest results showed that the experimental group achieved significantly higher scores (mean = 86.63) compared to the control group (mean = 74.73). The t-test results (Sig. < 0.05) indicated a significant difference, confirming that the use of the podcast has a positive impact on students' speaking skills. These findings support the theory that authentic audio media such as podcasts can improve students' fluency, pronunciation, vocabulary, and confidence in speaking English. This study proves that the Speak English Today podcast is effective as a learning medium for improving the speaking skills of MTs students.